Young children's screen habits and first-time parents' reflections on screen use in socioeconomically disadvantaged Swedish settings: a mixed methods study - Kirsi Tiitinen Mekhail; Lisa Blom; Lise-Lott Rydström (BMC, 2024)
Abstract Background Despite WHO's recommendation of limited screen time for children < 2 years, they are worldwide established screen users. Several negative consequences are connected to excessive screen use among children. As parents are key actors in introducing screens to children, it is important to explore children's screen habits and parents' perspectives on screen in different populations, which could support the development of guidelines for healthier screen use. This study aimed to explore young children's screen use habits and describe first-time parents' reflections on children's screen use in socioeconomically disadvantaged Swedish settings. Methods This mixed methods study was a part of larger studies within Stockholm County. The data were collected through semi-structured questionnaire-based interviews, among first-time parents (N = 386) of 15-18 months-olds at local Child Health Care centres during 2019-2022. Quantitative and qualitative data analyses conducted in parallel resulted in descriptive statistics and qualitative categories. Results Most children (92.4%) used screens by the age of 15-18 months, commonly for a maximum of 30 min (48.5%) per day. Participants stated the most suitable age for starting screen use to be after (41.7%) or at (37.9%) the age of two years. Parents' reflections on screen use formed three main categories, each having two sub-categories: screen use patterns (screen-related time and reasons for screen use), perceived concerns with screen use (child development and social issues), and attitudes related to screen use (parents' attitudes towards screens and child's response to screens). Conclusions First-time parents in socioeconomically disadvantaged settings expressed awareness of possible negative screen-related effects and recommendations but did not always focus on long-term consequences when using screens in everyday life. Screens used as a short distraction, time spent together with screens, infants' contact with relatives overseas, and pedagogical children's programs and apps can be regarded as screen-related benefits. Encouraging parents' self-reflection on their screen use may be a way of contributing to healthier screen habits among young children. Future studies are suggested regarding parents' and children's excessive interest in screens and how to manage screen use as a family. Trial registration Retrospectively registered 18 February 2020 (ISRCTN10336603) and 24 May 2021 (ISRCTN66190787) in ISRCTN registry.